The religious order as illiberal heterotopia?: human rights and contemporary Catholic monasticism - Potz, Maciej (Religion and human rights, 2025)
In the West, Catholic religious orders function within liberal political systems, yet are founded on a radically different set of values: they are communitarian rather than individualistic, rely on strong authority, and create total social structures with permanent control of behaviour. As a consequence, it is often charged that the monastic environment is inconsistent with human rights, because of its oppressive disciplinary practices and unacceptable self-deprivation of dignity it entails. Using IDIs conducted in Polish monastic institutions, I provide an empirical account of the extent to which they restrict freedoms and explain how members make sense of their situation. Is the monastery a human rights-exempted, “exterritorial” social space—a kind of Foucauldian heterotopia? Is living there an oppressive or a liberating experience? Sociologically, religious orders, especially contemplative, are total and greedy organizations, seriously restricting members’ freedom of movement, correspondence, private property etc. However, the members’ self-perception is shaped by different considerations, such as voluntariness of joining and remaining in the organization; striving for supernatural goals to which monastic discipline leads; the considerable political agency they enjoy; and the emancipatory character of monastic life many, especially women report. These accounts suggest that, cases of abuse and violations of basic rights notwithstanding, monasticism as such does not contravene the subjects’ interests and, thus, the human-rights critique is not entirely justified.